Correlation of Neopterin and TNF-alpha with Asymmetric Dimethylarginine in Metabolic Syndrome - Dedeh Yuniarty; Anwar Santoso; Mansyur Arif (The Indonesian Biomedical Journal, 2011)
BACKGROUND: A large number of obesity in the community increases the incidence of Metabolic Syndrome (MetS) that can increase the risks of heart disease, diabetes, and stroke. One of the possible causes of stroke is atherosclerosis. Atherosclerosis is initiated by the incidence of inflammation and endothelial dysfuction. Atherosclerosis is involved in an ongoing inflammatory response. At the beginning of atherosclerosis, when the endothel become inflamed, it expresses adhesion molecules  that attract monocytes. The monocytes then migrate into the intima due to endothelial dysfunction. Activation of macrophage occurs in the process of inflammation as the earliest type of lesion of atherosclerosis. In this study, monocyte/macrophage activation is marked by Neopterin. In other process of atherosclerosis, vascular nitric oxide (NO) activity has a role as a potent endogenous vasodilator. In regulating the vascular tone, NO has a role to suppress vascular smooth muscle proliferation, inhibit platelet adhesion and aggregation, and interferes with the leukocyte-endothelial cell interaction. In MetS, hypercholesterolemia decreases NO activity. Asymmetric Dimethylarginine (ADMA) has been characterized as an endogenous, competitive inhibitor of NO synthase. In this study, the incidence of endothelial dysfunction is marked by ADMA. The aim of this study was to discover the role of Neopterin in MetS patients by evaluating the correlation between Neopterin and ADMA in MetS through tumor necrosis factor (TNF)-α or direct line.METHODS: The study was cross sectional on 64 males with MetS aged 30-65 years. The measurements of TNF-α concentrations was done, respectively.RESULTS: Neopterin concentration correlated with Log TNF-α concentration (r=0.311, p=0.012). There is no significant correlation between Neopterin and ADMA (r=0.012, p=0.930); ADMA and Log TNF-α (r=0.029, p=0.821).CONCLUSIONS: There is no significant correlation between Neopterin and ADMA through TNF-α or direct line.KEYWORDS: MetS, Neopterin, ADMA, NO, TNF-α